Mapping and screening of the tomato Stemphylium lycopersici resistance gene, Sm, based on bulked segregant analysis in combination with genome resequencing - Huanhuan Yang; Tingting Zhao; Jingbin Jiang; Songbo Wang; Aoxue Wang; Jingfu Li; Xiangyang Xu (BMC Plant Biology, 2017)
Abstract Background Tomato gray leaf spot disease caused by Stemphylium lycopersici (S. lycopersici) is considered one of the major diseases of cultivated tomatoes. The only S. lycopersici resistance gene, Sm, was derived from the wild tomato species S. pimpinellifolium. Sm has been identified as an effective source of gray leaf spot resistance in tomatoes and has been mapped to tomato chromosome 11. In this study, the first bulked segregant analysis (BSA) combined with genome resequencing for the mapping and screening of the Sm candidate gene was performed. Results Based on the resequencing results, we identified 50,968 Diff-markers, most of which were distributed on chromosome 11. A total of 37 genes were located in the interval of 0.26-Mb. The gene loci of resistant and susceptible lines were sequenced successfully using PCR products. The relative expression levels of candidate genes in resistant and susceptible lines were confirmed via qRT-PCR, Solyc11g011870.1.1 and Solyc11g011880.1.1 were identified through qRT-PCR. A marker, D5, which was cosegregated with the resistant locus, was identified according to the mutation of the Solyc11g011880.1.1 trait in the resistant line. Conclusions The Sm gene was mapped to the short arm of chromosome 11. The candidate genes Solyc11g011870.1.1 and Solyc11g011880.1.1 displayed expression patterns related to the resistance response. This study will be valuable for Sm cloning and Sm gene breeding in tomato.